Impaired Cytokine Responses to Epstein-Barr Virus Antigens in Systemic Lupus Erythematosus Patients. (27th March 2016) - Draborg, Anette Holck; Sandhu, Noreen; Larsen, Nanna; Lisander Larsen, Janni; Jacobsen, Søren; Houen, Gunnar
Abstract : We analyzed cytokine responses against latent and lytic Epstein-Barr virus (EBV) antigens in systemic lupus erythematosus (SLE) patients and healthy controls (HCs) to obtain an overview of the distinctive immune regulatory response in SLE patients and to expand the previously determined impaired EBV-directed T-cell response. The concentrations of 14 cytokines (IL2, IL4, IL5, IL6, IL10, IL12, IL17, IL18, IL1 β, IFN γ, TNF α, TNF β, TGF β, and GM-CSF) were quantified upon stimulation of whole blood with latent state antigen EBNA1, lytic cycle antigen EBV-EA/D, and the superantigen SEB. To avoid results affected by lack of lymphocytes, we focused on SLE patients with normal levels. Decreased induction of IL12, IFN γ, IL17, and IL6 upon EBNA1 stimulation and that of IFN γ, IL6, TNF β, IL1 β, and GM-CSF upon EBV-EA/D stimulation were detected in SLE patients compared to HCs. IFN γ responses, especially, were shown to be reduced. Induction of several cytokines was furthermore impaired in SLE patients upon SEB stimulation, but no difference was observed in basic levels. Results substantiate the previously proposed impaired regulation of the immune response against latent and lytic cycle EBV infection in SLE patients without lymphopenia. Furthermore, results indicate general dysfunction of leukocytes and their cytokine regulations in SLE patients.